A Preliminary Study of Mosses as Biomonitors of 137Cs Activity in the Air of Ioannina City - Stamoulis, K.; Alexandropoulou, M.; Petsios, S; Papachristodoulou, C. A.; Papadopoulou, C.; Ioannides, K. G. (HNPS Advances in Nuclear Physics, 2019)
Mosses were collected during the winter months of 2014 and 2015 from various locations in the center and outskirts of the city of Ioannina, to serve as biomonitors of 137Cs activity released from the combustion of biomass fuel in the atmospheric air. Statistical analysis of the obtained activity concentrations revealed differences between sampling locations and sampling periods, which may be attributed to different practices in the use of wood and wood by-products fuel for household heating.